Five Technologies for Detecting the EGFR T790M Mutation in the Circulating Cell-Free DNA of Patients With Non-small Cell Lung Cancer: A Comparison - Chen, Yi-Lin; Lin, Chien-Chung; Yang, Shu-Ching; Chen, Wan-Li; Chen, Jian-Rong; Hou, Yi-Hsin; Lu, Cheng-Chan; Chow, Nan-Haw; Su, Wu-Chou; Ho, Chung-Liang (Frontiers in Oncology, 2019)
Third-generation tyrosine kinase inhibitors (TKIs) were developed to overcome T790M-mediated resistance to earlier generations of epidermal growth factor receptor (EGFR)-targeted TKIs. We compared four well-established and one in-house method for the analysis of the EGFR T790M mutation in plasma cell-free DNA (cfDNA), in hope to find a better way to select non-small cell lung cancer (NSCLC) patients appropriate for 3rd-generation TKI therapy. For sensitivity levels of each method, plasmid DNA with EGFR T790M mutations was serially diluted with cfDNA from healthy controls with wild type EGFR. The clinical performance was analyzed in a clinical cohort of EGFR mutation-positive NSCLC patients with acquired EGFR TKI resistance (n = 40). All methods except the therascreen kit (Qiagen) had a sensitivity level of 10 copies of T790M plasmid DNA in the spiked specimen. The detection rates of the EGFR T790M mutation in plasma cfDNA from the clinical cohort were 42.5, 35, 32.5, 22.5, and 17.5% for the in-house ARMS method, Bio-Rad droplet digital PCR, PANAMutyper, Therascreen EGFR Plasma RGQ PCR Kit and Cobas EGFR Mutation kit (with suboptimal template amounts), respectively. Osimertinib was given to 17 of 20 patients with EGFR T790M mutations. The best treatment responses, based on the RECIST criteria, included 6 partial responses (PR) and 7 stable diseases (SD). The PANAMutyper and the Bio-Rad droplet digital PCR were comparable, the Cobas EGFR Mutation kit required significantly more template for testing. The best combination would be the in-house ARMS method plus the PANAMutyper or Bio-Rad droplet digital PCR, which would have a detection rate of 50% (20/40) and a disease control rate of 76% (13/17).